Effect of DS-2969b, a novel GyrB inhibitor, on rat and monkey intestinal microbiota. (June 2018) - Kumar, Manoj; Mathur, Tarun; Joshi, Vattan; Upadhyay, Dilip J.; Inoue, Shin-ichi; Masuda, Nobuhisa
Abstract: DS-2969b, a novel GyrB inhibitor, transiently and reversibly altered the counts of limited intestinal microbiota at around 10 μg/g of faecal levels in rats and monkeys. Considering the high activity of DS-2969b against Clostridium difficile, 10 μg/g of faecal levels would be sufficient for clearing C. difficile from the intestine. Highlights: DS-2969b is being developed for Clostridium difficile treatment. DS-2969b has potent activity against C. difficile epidemic NAP1/027 strains. The impact of DS-2969b on microbiota and efficacious fecal level was evaluated. DS-2969b showed a transiently effect on microbiota at ∼10 μg/g of fecal level.